Letter - Atholl, Katharine Marjory Stewart-Murray, Duchess of, 1874-1960
1943-10-11 038-0016-002 children remain in this country. A regular income of £200/300 a month is necessary to carry on the work as, although many of the children can help to support themselves, they still need partial maintenance to supplement the money they can earn. Will you help in this urgent work which is something even more than humanitarian - in fact, one more opportunity to contribute to the building of a new and better world. The thought that this young generation of Spain will carry away experience and friendships which must work for international understanding and goodwill in their own country or wherever they may emigrate in the years to come, and their real gratitude for the help we give, are our inspiration and joy in the work. Will you share this with us? Every penny you give will be wisely and economically spent. Yours sincerely, Katharine Atholl President. 292/946/38/16(II)